'And she calls herself a woman' : Criticising the New Woman in the British Periodical Press of the 1890s - Sarenius, Melissa (My University, 2025)
In this dissertation I look at the ways in which the New Women were described and criticised by their opponents in the British periodical press of the 1890s. To do this, I will use close reading to study five articles that were published in The Nineteenth Century, Blackwood’s Edinburgh Magazine, The Quarterly Review and The Cornhill Magazine by four different authors: Eliza Lynn Linton, Hugh E. M. Stutfield, W. F. Barry and an anonymous author. In the articles I have chosen to study the New Women are described as posing a threat to the established rules and codes of society; they are overtly conscious of their sexuality and not afraid to discuss it openly, they have an unusual interest in education and work, they pepper their speech with slang words, they smoke cigarettes, ride bicycles, hunt, play golf and cricket, dress in either rational dress or tailormade clothing, and are described as being varyingly overtly attractive or wholly unattractive; all in all, they are unlike any other, decent female contemporaries of theirs, and participate in activities wholly unsuitable for women of their time. And yet, despite all their masculine transgressions the New Women, in the words of the anonymous author, still had the audacity to call themselves women.
Keywords: the New Woman, Feminist history, Women’s history, the 1890s, ‘the naughty nineties’, fin de siècle, the periodical press, Great Britain